Conducting a Process Evaluation in Nonprofit and Governmental Programs: FCS3370/FY1509, 5/2022 - Barajas Espinosa, Marlen; Richardson, Micayla; DeMasters, Chelsea; Jones, Jennifer A.; Wiley, Kimberly (EDIS, 2022)
The purpose of a program evaluation is to assess a program’s performance. This article explains how to (1) identify which type of failure nonprofit organizations may be facing, (2) choose the right evaluation tool in order to determine the specific problem, (3) interpret process evaluation results, and (4) use the evaluation findings for continuous program improvement. Written by Marlen Barajas Espinosa, Micayla Richardson, Chelsea DeMasters, Jennifer A. Jones, and Kimberly Wiley, and published by the UF/IFAS Department of Family, Youth and Community Sciences, May 2022.